Self-directed learning in emerging adulthood: developmental and biographical reflections - Güvercin, Gökçe (Adult Education Discourses, 2023)
Self-directed learning is a skill woven through specific life experiences. Based on biographical narratives, this study focuses on the self-directed learning skills of emerging adults who are university students and aims to provide an understanding of the background dynamics of different learning orientations. Theoretical sampling was used to conduct biographical narrative interviews. The Documentary Method was employed to interpret the interviews. The results of the documentary analysis of the narratives put that the autonomy-supportive family structure throughout the life course and the individual’s willingness and desire to be autonomous constitute an important and decisive ground for the emotional dimension of self-directed learning skills. The research findings also reveal that self-directed learning is a way of life and a set of continuous processes that require continuity far beyond the boundaries of formal education. The research findings can be convenient in two ways. First, families can recognise and support an adolescent’s effort and need to separate and contribute to the relationship dynamics necessary for their children to become self-directed learners. Second, the findings of the research suggest that more than a technical skill within the boundaries of formal education, self-directed learning is a positioning in life, which may lead to a holistic approach in future research on the subject.